CHARACTERIZATIONS OF JOKER: A COMPARISON OF TWO BATMAN FILMS - Wardhaningsih, Ni Made Mira (2017)
Batman franchise is one of the most watched franchises in the history of cinema (Box Office Mojo, 2016). There are at least nine film adaptations of Batman, not including the direct-to-video films, animated films, and television series. There are more than one version of the characters which are consumed by the audience. This study seeks to investigate the portrayals of the Batman villain character Joker in two Batman films entitled Batman (Burton, 1989) and The Dark Knight (Nolan, 2008). Using a qualitative descriptive method, this study employs Boggs and Petrie's (2008) framework of characterization in films as its analytical tool. Some of Bordwell and Thompson's (2010) cinematic techniques (i.e., mise-en-scene, camera shot and angle, and sound) are used to strengthen the analysis. The analyses of the portrayals are used to find the signification. The analyses show that the portrayals of Joker have similar traits. However, the portrayals also possess significant differences. Joker in Batman seems to depict human's corrupted traits whereas Joker in The Dark Knight implies that he is an embodiment of terror. The character Joker is portrayed differently in two different films in order to signify different fears which are circulated in two different time periods. This study reveals that characters based on the same source can signify different representations of fear within the society due to the different time periods the films were produced.;---Serial Batman adalah salah satu serial film yang paling banyak ditonton sepanjang sejarah perfilman (Box Office Mojo, 2016). Setidaknya terdapat sembilan adaptasi dari Batman, tidak termasuk film animasi, serial televisi, atau film direct-to-video. Terdapat lebih dari satu versi karakter-karakter Batman yang dikonsumsi oleh penonton. Studi ini bermaksud untuk menginvestigasi peran dari tokoh penjahat Batman yaitu Joker dalam dua film-film Batman berjudul Batman (Burton, 1989) and The Dark Knight (Nolan, 2008). Menggunakan metode kualitatif deskriptif, studi ini memakai kerangka karakterisasi film milik Boggs and Petrie (2008) sebagai alat analisanya. Beberapa teknik perfilman dari Bordwell dan Thompson (2010) (i.e., mise-en-scene, sudut dan pengambilan kamera, dan suara) juga digunakan untuk memperkuat analisa. Analisa dari peran-peran tersebut kemudian digunakan untuk mecari signifikansi. Analisa menunjukkan bahwa kedua peran Joker memiliki sifat yang mirip. Meskipun demikian, peran-peran tersebut juga menunjukkan perbedaan yang besar. Joker dalam Batman tampak menunjukkan sifat jelek manusia sedangkan Joker dalam The Dark Knight mengimplikasikan bahwa ia adalah personifikasi terror. Karakter Joker diperankan berbeda dalam dua film tersebut untuk memberikan signifikansi perbedaan symbol ketakutan yang muncul di dua zaman yang berbeda. Studi ini membuktikan bahwa karakter-karakter yang diadaptasi dari sumber yang sama dapat menunjukkan representasi ketakutan yang berbeda dalam masyarakat dikarenakan perbedaan zaman di mana film tersebut diproduksi.